Thermal effect of a fire on a steel beam with corrugated wall with fireproof mineral-wool cladding - Valeriia Nekora (PC Technology Center, 2021)
This paper reports a study into the possibility of applying a simplified approach, recommended by standards for conventional steel beams, to determine the heating temperature under the conditions of a fire in relation to steel I-beams with a corrugated wall. The research is predetermined by the limitation of methods that make it possible to determine the heating temperature of this type of beam in a fire using engineering methods with a small amount of calculations.